A polyaspartic acid sodium interfacial layer enhances surface trap passivation in perovskite solar cells. Issue 41 (11th June 2019) - Wang, Boxin; Wu, Fei; Bi, Shiqing; Zhou, Jiyu; Wang, Jianqiu; Leng, Xuanye; Zhang, Dongyang; Meng, Rui; Xue, Baoda; Zong, Chengzhong; Zhu, Linna; Zhang, Yuan; et al.
Abstract : A biopolymer PASP layer works effectively to passivate the surface traps in MAPbI3 perovskite solar cells. Abstract : The characteristics of perovskite solar cells (PSC) are affected by interface traps. In this work, we introduce an interfacial modifier based on polyaspartic acid sodium (PASP) that is incorporated between a methylammonium lead iodide (MAPbI3 ) photo-absorber and P3CT-Na hole transporting layer. PASP contains a large number of –COO − anions and Na + cations, thus enabling a strong chelating cooperation for metal polyvalent ions. The incorporated PASP leads to an effective passivation of the surface traps originating from Pb 2+ and I − in MAPbI3 and control over the crystallization of MAPbI3 with slightly enlarged grains. The combined benefits with the introduced PASP enable boosting the power conversion efficiency to 20.05% with an impressive FF of 82.20% in MAPbI3 based p–i–n PSCs.